A Novel Method for Assemblability Evaluation of Non-Ideal Cylindrical Parts Assembly. (May 2021) - Li, Yue; Qiao, Lihong; Huang, Zhicheng; Anwer, Nabil
Abstract: The assemblability, which is the feasibility and difficulty of assembly, will greatly affect the efficiency and quality of assembly process, so assemblability analysis plays an important role during the design stage of products. Cylindrical parts assembly is a common structure with wide applications, whose assemblability can be affected by surface deviations, especially in some precision assemblies. In this paper, a novel method is proposed for the assemblability evaluation of cylindrical parts assembly considering surface deviations. Firstly, based on the surface deviations modeling of cylindrical parts and assembly clearance calculation, the assembly posture adjustment process is defined and simulated to obtain the assemblable postures without interference between parts. Then, in the proposed six dimensional posture space, a search algorithm is established to obtain the boundary points of assemblable posture space. Afterwards, in order to represent this irregular hyperspace, the largest inscribed generalized cone of which is put forward. Finally, based on the characteristics of generalized cone, two indicators are defined to reflect the adjustable range of assembly posture, which can realize the quantitative evaluation of assemblability. The validity of the proposed method is verified by case studies of cylindrical parts assemblies with different surface deviations. Highlights: Assemblability analysis plays an important role in the design stage of products. Assemblability of cylindrical assembly can be greatly affected by surface deviations. Method for assemblability evaluation of non-ideal cylindrical parts assembly considering surface deviations is proposed. The method evaluates the assemblability based on the assembly posture adjustment process. Applications of assemblability evaluation of cylindrical assemblies with different surface deviations are given.